2020
DOI: 10.2147/rmhp.s277521
|View full text |Cite
|
Sign up to set email alerts
|

<p>Reduced Intellectual Ability in Offspring Born from Preeclamptic Mothers: A Prospective Cohort Study</p>

Abstract: Background: Severe preeclampsia may affect placental development, and high homocysteine (Hcy) levels are linked to intellectual disability. However, the correlation between perinatal Hcy levels and intellectual ability remains unknown in severe preeclampsia-affected offspring. Objective: We aimed to investigate the intellectual ability in offspring born from preeclamptic mothers and examine the role of prenatal Hcy in the prediction of intellectual disability in preschool-aged offspring. Methods: The IQ scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…30 A prospective cohort study conducted in China using the Chinese Wechsler Young Children Scale of Intelligence showed that the offspring of mothers with severe PE had 2.86 higher prevalence of intellectual disability than infants born to normotensive mothers. 31 A case-control study of children aged 24-60 months found association between severe PE, autism spectrum disorder and many forms of developmental delay, as confirmed by the Mullen Scales of Early Learning and the Vineland Adaptive Behavior Scales. 32 A systematic review including 45 observational studies reported a significant association of gestational hypertension with lower cognitive function and higher BP in the offspring.…”
Section: Discussionmentioning
confidence: 93%
“…30 A prospective cohort study conducted in China using the Chinese Wechsler Young Children Scale of Intelligence showed that the offspring of mothers with severe PE had 2.86 higher prevalence of intellectual disability than infants born to normotensive mothers. 31 A case-control study of children aged 24-60 months found association between severe PE, autism spectrum disorder and many forms of developmental delay, as confirmed by the Mullen Scales of Early Learning and the Vineland Adaptive Behavior Scales. 32 A systematic review including 45 observational studies reported a significant association of gestational hypertension with lower cognitive function and higher BP in the offspring.…”
Section: Discussionmentioning
confidence: 93%
“…Emodin (1,3,8-Trihydroxy-6-methylanthra-quinone) is a natural product, which originates from Rheum palmatum. Previous studies have reported that emodin exhibits anti-inflammatory effects (8,9). In addition, it has been revealed that emodin can alleviate the symptoms of AP (10).…”
Section: Introductionmentioning
confidence: 96%